2012
DOI: 10.1186/1756-0500-5-405
|View full text |Cite
|
Sign up to set email alerts
|

Promoting community knowledge and action for malaria control in rural Cambodia: potential contributions of Village Malaria Workers

Abstract: BackgroundCambodia has been investing in Village Malaria Workers (VMWs) to improve malaria case management in rural areas. This study assessed the quality of the VMWs’ services compared to those by a government-run health center from the perspective of community members. We focused on VMWs’ contribution to promote their action to control malaria. A community-based cross-sectional study was conducted in Kampot province in 2009. Interviews were conducted at every accessible household in a village with VMWs (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Greater awareness about malaria and undertaking a broader range of preventive actions for malaria influence appropriate treatment-seeking behaviour. A study in Cambodia showed that early recognition of malaria symptoms is the first important step to treatment seeking [ 20 ]. In the present study, although caregivers were aware of malaria symptoms, about 50% were unaware that children under five and pregnant mothers are especially vulnerable to malaria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Greater awareness about malaria and undertaking a broader range of preventive actions for malaria influence appropriate treatment-seeking behaviour. A study in Cambodia showed that early recognition of malaria symptoms is the first important step to treatment seeking [ 20 ]. In the present study, although caregivers were aware of malaria symptoms, about 50% were unaware that children under five and pregnant mothers are especially vulnerable to malaria.…”
Section: Discussionmentioning
confidence: 99%
“…A structured questionnaire was developed based on the WHO Malaria Indicator Survey tool [ 19 ] and relevant studies [ 20 23 ]. The questionnaire was first developed in English, translated into Myanmar language, and translated back into English by experts on public health and malaria in Myanmar.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size of caregiver participants was calculated using Power and Precision software (Biostat, Englewood, New Jersey, USA), based on 40% VMW service utilization in M villages [28] and the assumption of an approximately 10% higher utilization in M+C villages, with alpha set at 0.05 and 80% power. This resulted in a minimum sample size of 388 caregivers to be surveyed per service type.…”
Section: Methodsmentioning
confidence: 99%
“…The VMW project has improved knowledge and practices of VMWs to prevent malaria and to provide early diagnosis and treatment in remote malaria endemic villages [16,27]. VMWs can now provide malaria control services comparable in quality to those of the local health facilities [28]. In March 2011, the government of Cambodia formally committed itself to eliminate malaria by the year 2025, identifying the VMW project as one of the key strategies to meet that goal [4].…”
Section: Introductionmentioning
confidence: 99%